The potential of 1,2,4-triazole derivatives as antioxidant agents (literature review) - V. O. Salionov; H. P. Smoilovska (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
1,2,4-Triazoles are important compounds in organic and pharmaceutical chemistry, which are known for their high reactivity and biological activity. They show a wide range of pharmacological properties with minimal toxicity. A promising area of research is the use of 1,2,4-triazole derivatives as antioxidants. 1,2,4-Triazoles are notable for their ability to neutralize free radicals and other reactive oxygen forms, which can damage cells and tissues.